Binding of a single divalent cation directly correlates with the blue-to-purple transition in bacteriorhodopsin. - Jonas, R (1991)
We have characterized a unique divalent cation binding site on bacteriorhodopsin which controls the blue-to-purple transition in the purple membrane of Halobacterium halobium. To identify this site we first showed the correlation between the binding of one Ca2+ per bacteriorhodopsin and the amount of blue membrane converted to purple membrane. When the free Ca2+ was reduced below 1 microM, and the pH was set below 5.0 with 0.5 mM citrate, only binding to this high-affinity site was observed, and we could separate its effect from the effect of other divalent cations binding to the membrane under other conditions. Second, the titration of purple membrane showed that protons are taken up in two distinct steps, about 13 with a pKa of 4-5 and an additional 2 protons with a pKa of 2.75, in 5 mM MgSO4. The latter is identical to the pKa for the purple-to-blue transition in 5 mM MgSO4. Taken together, these observations strongly suggest a direct role for cations in the regulation of the bacteriorhodopsin color under normal conditions. We have also found that the intrinsic pKa for the purple-to-blue transition is about 2.05, suggesting this is the pKa of the group or groups that, when protonated, lead to the blue membrane. Previously published data can now be interpreted to suggest that the cation regulates an active site near the retinal chromophore. A binding site for the divalent cation that includes Asp-212 and interactions with the protonated Schiff base, Asp-85, Tyr-57, Tyr-185, and Arg-82 is proposed.